DARI GENERASI KE GENERASI: MENGUAK PERBEDAAN IDENTITAS SAINS MAHASISWA PGSD - Siti Zahra Mulianti Natsir (STKIP Subang, 2026)
This study aims to reveal the differences in science identity among elementary teacher education (PGSD) students from three cohorts—2023, 2024, and 2025—based on the PISA 2025 science literacy framework. A quantitative comparative approach was applied with 159 participants selected through proportionate stratified random sampling. The science identity questionnaire consisted of three sub-domains: appreciation of diverse perspectives in scientific inquiry, positive attitudes toward self-identification as part of the scientific community, and awareness and active engagement toward the environment. Data were analyzed using the Kruskal–Wallis test because the data were not normally distributed. The results showed a significant difference in science identity among cohorts (p = 0.013). Post-hoc analysis indicated that students from the 2023 cohort had significantly higher science identity scores than those from the 2025 cohort (p = 0.010), while no significant differences were found between the 2024 cohort and the other two. The findings suggest that students with longer exposure to practical and inquiry-based science learning develop stronger scientific self-efficacy, engagement, and recognition within the science community. Laboratory and inquiry activities provide authentic experiences that foster a sense of belonging and strengthen science identity. Therefore, meaningful scientific experiences—whether through direct or virtual laboratories—are essential in nurturing science identity among pre-service elementary teachers. These results emphasize the need for early integration of experimental and investigative learning to prepare scientifically literate and confident future educators.